Metabolite Identification and Pharmacokinetic Behavior of Diaveridine in the Plasma of Pigs and Chickens Based on Radioactive Tracing Coupled With LC/MS-IT-TOF Assay - Wang, Liye; Wen, Lihua; Pan, Yuanhu; Wang, Zhenzhen; Zhou, Kaixiang; Mi, Kun; Liu, Zhenli; Qu, Wei; Huang, Lingli (Frontiers in Veterinary Science, 2022)
Diaveridine (DVD) is widely used for the prevention and treatment of coccidiosis and leucocytozoonosis infections in food-producing animals. To gain a better understanding of DVD metabolism and pharmacokinetics in healthy Landrace/Doric Cross castrated male pigs and both female and male Cobb 500 broiler chickens, a method involving radioactive tracing coupled with LC/MS-IT-TOF was developed for the identification and quantitation of DVD and its metabolites in pig and chicken plasma, and then was applied to investigate DVD pharmacokinetics. A simple MCX solid phase extraction procedure was adopted for sample preparation. After a single oral administration of 3H-DVD (10 mg/kg BW), three radioactive compounds (D0: DVD; D1: 3′-desmethyl-DVD; and D2: monoglucuronide of 3′-desmethyl-DVD) were identified in pig plasma, while only two radioactive compounds (D0 and D2) were identified in chicken plasma. In both species, the Cmax values for all detected compounds were reached at 2 h after dosing. The Cmax order was D2 (1.38 μg/mL) > D0 (0.49 μg/mL) > D1 (0.24 μg/mL) in pigs and D0 (1.55 μg/mL) > D2 (0.27 μg/mL) in chickens. The longer t1/2 (elimination half-life) of D0 contributed to the slow elimination of DVD-related compounds. The t1/2β of D0 in pigs (66.41 h) was significantly longer than that in chickens (48.30 h), but the t1/2 of total DVD-related metabolites in pigs (42.86 h) was lower than that in chickens (56.11 h). These findings suggested that the metabolism and pharmacokinetics of DVD in pigs and chickens were significantly different, and that this would affect its effectiveness, toxicology, and food safety in these animals.